Gene expression profiles of transient receptor potential (TRP) channels in the peripheral blood mononuclear cells of psoriasis patients - Özcan, SS; Gürel, G; Çakır, M (Human & experimental toxicology, 2021)
Psoriasis is a chronic autoimmune disease in which peripheral blood mononuclear cells (PBMCs) are involved in the pathological process. Transient receptor potential (TRP) channels expressed in immune cells have been shown to be associated with inflammatory diseases. We aimed to evaluate mRNA expression levels of TRP channels in PBMCs of patients with psoriasis. 30 patients with plaque psoriasis and 30 healthy age- and gender-matched control subjects were included in this study. mRNA expression levels of TRP channels in psoriasis patients were determined by Real-time polymerase chain reaction. A decreased TRPM4, TRPM7, TRPV3, TRPV4, and TRPC6 genes expression levels were found in the patient group compared to controls, respectively (p = 0.045, p = 0.000, p = 0.000, p = 0.045, p = 0.009), whereas, an increased expression level was found in TRPM2 and TRPV1 genes in the patient group compared to controls (p = 0.001 and p = 0.028). This is the first study showing the TRP channel mRNA expressions in PBMCs of psoriasis patients. Different expression patterns of TRP channels may have a role in pathogenesis of psoriasis.